Patient experiences with general practice in Norway: a comparison of immigrant groups and the majority population following a national survey - Marte Kjøllesdal; Thor Indseth; Hilde Hestad Iversen; Oyvind Bjertnaes (BMC, 2020)
Abstract Background Patient experience is an important indicator of quality of health care. In Norway, little is known about the quality of health care for immigrants. The aim of this study was to compare patient-reported experiences with general practice between the Norwegian-born population and immigrant groups. Methods We performed secondary analyses of data from a national survey on patient experiences with general practice, including assessments of general practitioners (GPs) and their GP offices. The survey was carried out in Norway in 2018-19. The total number of respondents was 2029, with a response rate of 42.6%. Region of birth was available for 1981 participants, and these were included in the analyses ("Norway" (N = 1756), "Asia, Africa or South America" (N = 95), "Eastern Europe" (N = 70) and "Western Europe, North America or Oceania" (N = 60)). Five indicators of patient experiences were used as dependent variables in bivariate and multivariate analyses, with region of birth as the main exposure variable and other background variables about the patient as adjustment variables: "the GP" (measures related to communication and competency), "auxiliary staff" (politeness, competency, organization), "accessibility" (waiting times), "coordination" (with other services) and `enablement` (GP facilitates coping with/understanding illness). Results Immigrants as a whole reported poorer experiences with general practice than the majority population, with significantly poorer scores on four of five patient experience indicators. Patients from Asia/Africa/South America reported poorer experiences than those from Norway on the indicators "GP", "auxiliary staff", "accessibility" and "coordination": on a scale from 0 to 100 where 100 is the best, the difference ranged from 7.8 (GP) to 20.3 (accessibility). Patients from Eastern Europe reported lower scores on "GP" and patients from Western Europe/North America/Oceania reported lower scores on "auxiliary staff". These associations were still significant after adjustment for sex, age, self-rated physical and mental health, number of contacts with the GP and education. Conclusions For countries with a substantial proportion of foreign-born patients in the health system, immigrant background is an important parameter in quality improvement work. Immigrant background is also an important parameter in health service research.